Governance models and port concessions in Europe: Commonalities, critical issues and policy perspectives. (July 2015) - Ferrari, Claudio; Parola, Francesco; Tei, Alessio
Abstract: The paper analyses European port regulation, focusing primarily on the effectiveness of concession agreements in the port sector. Current heterogeneity in EU port regulation is widely recognised as having an impact on the competitiveness of ports. Moreover, Port Authorities have to take into account a wide range of goals in order to manage the interactions with private operators responsible for port activities. Thus, some trade-offs emerge, as in some cases a revenue stream or a strategic objective for the Port Authority may imply a cost for the concessionaire. This paper discusses how concession agreements can contribute to regulating these trade-offs.